Skeletal, Dental and Soft Tissue Effects of Twin Block Appliance in Different Facial Divergence Cases - Jha, Kanistika; Adhikari, Manoj; Panthee, Pratikshya (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Class II malocclusions refer to a discrepancy in the sagittal plane associated with either backward or upward rotation of the jaw. A backwardly positioned mandible is usually managed using a Twin block appliance which contains a bite plane to direct the occlusal forces in a more favorable direction. Our aim was to evaluate skeletal, dental, and soft tissue changes using twin-block appliance therapy in different facial divergence patients. Methods A cephalometric study was conducted among two groups with 15 patients in each group. Group 1 have a Frankfort Mandibular plane Angle (FMA) of 18-25 degree while Group 2 have an FMA of 28 to 33 degree with Class II Division I malocclusion. All of them were treated with twin block appliances with modifications done according to FMA. Cephalometric analysis was done using Dolphin software (Dolphin Imaging 11.95) to evaluate skeletal, dental, and soft tissue changes after twin block therapy. Results Analysis of variance and paired t-test were used to evaluate pre and post-treatment changes in cephalograms. The position of the mandible, maxillomandibular relation, and mandibular length was changed by 3.99 degrees, 5.23 degrees, and 4.04mm respectively in horizontal growers, while by 2.9 degrees, 1.74 degrees, and 1.07mm respectively in vertical growers. An increment in FMA by 4.59 degrees in horizontal growers with good vertical control and a little increment in FMA by 1.07 degrees in vertical growers were seen. Conclusions The twin block appliance is effective in skeletal, dental, and soft tissue correction in patients with different facial divergences.